Occupational diseases in the Czech Republic in the year 1998. The need for unifying European standards/criteria for all occupational diseases - Pelclová, D; Fenclová, Z; Lebedová, J (Central European journal of public health, 2000)
In the Czech Republic, the Clinics and Departments for Occupational Medicine according to the legislation have the right to recognise occupational diseases. The diagnosis must correspond to the Czech list of occupational diseases, which is similar to the European list of occupational diseases. The exposure, sufficient enough to cause certain occupational disease, must be confirmed by regional industrial hygienists, responsible for hygienic control of the workplace. It is evident that the number of diseases is very much dependent upon the standards/criteria used to recognise occupational diseases. In the Czech Republic, the patients suffering from occupational diseases are given considerable financial compensations, which creates a great motivation for them to apply for occupational diseases. The article presents the overview of occupational diseases in the Czech Republic in the year 1998. The total number of diseases was 2111, the incidence per 100,000 employees was 45.8. It is necessary to present and discuss unifying criteria for occupational diseases in European countries, as well as the minimum level of the damage, that could be called an occupational disease. The criteria should be co-ordinated, because in a unified Europe, there will be many more possibilities for change in the workplace.
Keywords: Occupational Exposure; Occupations; služby zdravotní péče o pracující; Humans; nemoci z povolání; Česká republika; pracovní lékařství; lidé; zaměstnání; Europe; pracovní expozice; Occupational Medicine; Evropa; incidence; Incidence; Occupational Diseases; Czech Republic; Occupational Health Services